The image of Central and Eastern Europe in Dutch literary nonfiction - Sterckx, Jo (Werkwinkel, 2014)
Over the last 20 years, literary nonfiction has become increasingly popular among the Dutch reading public. Thanks to increasing sales, translations and literary awards the genre achieved a strong position in Dutch literature. This article analyzes the image of Central and Eastern European countries in Dutch literary nonfiction of the last ten years (2004-14). It searches for characteristics of an orientalist and balkanist discourse and the presence of the imagological centre-periphery model in the works of Geert Mak, Jelle Brandt Corstius, Olaf Koens, Joop Verstraten and Jan Brokken. Contemporary Dutch literary nonfiction contains a euro-orientalist discourse. Characteristics such as underdevelopment, hedonism, obscurity and authenticity are projected on Central and Eastern Europe, which is put in the periphery of Western Europe.